2012
DOI: 10.1111/j.1365-2036.2012.05202.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: the efficacy and safety of pancreatin enteric‐coated minimicrospheres (Creon 40000 MMS) in patients with pancreatic exocrine insufficiency due to chronic pancreatitis ‐ a double‐blind, placebo‐controlled study

Abstract: SummaryBackgroundPancreatic exocrine insufficiency (PEI) results in maldigestion, leading to abdominal pain, steatorrhoea, malnutrition and weight loss.AimTo assess the efficacy and safety of pancreatin (Creon 40000 MMS) in treating PEI due to chronic pancreatitis (CP).MethodsThis was a 1-week, double-blind, randomised, placebo-controlled, parallel-group, multicentre study in India. Men and women ≥18 years of age with proven CP and PEI [defined as a coefficient of fat absorption (CFA) ≤80% during run-in phase]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 24 publications
1
46
1
5
Order By: Relevance
“…Improvement, but incomplete resolution of subjective and objective steatorrhea was reported. In addition, PERT also had a higher incidence of adverse drug reactions like pain, dyspepsia, and flatulence [81][82][83][84].…”
Section: Randomized Controlled Trials Of Pert In Patients With Pancrementioning
confidence: 99%
“…Improvement, but incomplete resolution of subjective and objective steatorrhea was reported. In addition, PERT also had a higher incidence of adverse drug reactions like pain, dyspepsia, and flatulence [81][82][83][84].…”
Section: Randomized Controlled Trials Of Pert In Patients With Pancrementioning
confidence: 99%
“…Study design and quality assessment are shown in table 1. There were four 32 33 40 45 conducted in the USA, nine 34-39 41 43 44 in Europe, two 46 47 in the USA and Europe, one 42 in South Africa and one 48 …”
Section: Design and Quality Assessment Of Included Studiesmentioning
confidence: 99%
“…Gender was reported in most studies ( pooled 76.4% males). Ethnicity was reported in only four [45][46][47][48]. None reported residence data, smoking, socioeconomic status or profession.Five 41 42 46-48 reported body mass index.…”
mentioning
confidence: 99%
“…The benefit of 90 000 USP U of pancreatin [two capsules of CREON (Abbott Laboratories, Abbott Park, Illinois) 40 000 containing 45 000 USP U lipase with meals and one capsule with snacks] compared with placebo was assessed in a multicenter, randomized controlled trial (RCT) in 62 patients with chronic pancreatitis and a coefficient of fat absorption (CFA) less than 80% [22 ■ ]. Pancreatin increased the CFA from 66.5 to 86.1% (mean change of CFA vs. placebo, 18.5 vs. 4.1%; P = 0.001) and the coefficient of nitrogen absorption (CNA) from 78.8 to 83.8% (mean change of CNA vs. placebo 4.7 vs. 0.8%; P = 0.005) and decreased stool frequency and weight.…”
Section: Management Of Exocrine Pancreatic Insufficiencymentioning
confidence: 99%